Preliminary Results about Growth Performance and Food Conversion Ratio of Acipenser stellatus juvenils, Fed with Different Dietary Protein Levels - Maria Desimira Dicu; Victor Cristea; Lorena Dediu; Mirela (Creţu) Mocanu; Ştefan Mihai Petrea; Adina Popescu (Scientific Papers Animal Science and Biotechnologies, 2023)
The main purpose of this study is to evaluate the effects of different dietary protein levels on Acipenser stellatus growth performance. Researches were conducted between 4 th November-3rd December 2011, in the recirculating system of Aquaculture, Environmental Science and Cadastre Department, University of Galati. A number of 60 fish with an average weight of 11.5±0.58 g were randomly stocked into four rearing units, with same stocking densities. Two experimental variants with different dietary protein levels, 64% (V1) respectively 41% (V2), were applied in duplicate. At the end of the experiment, the specific growth rate (SGR), calculated as mean value of both repetitions for each variant, was 4,64%/day at V1 and 4,63%/day at V2. Protein efficiency ratio PER (g/g) registered a better value at V2 (2.55 g/g), comparing to V1 (1.62 g/g). Regarding feed conversion ratio, almost identical values were observed in case of both experimental variants: 0,96 at V1 and 0.97 at V2. The final results of the experiment showed that while PER was significantly influenced by dietary protein levels, the rest of growing indicators had a very limited variation scale.